Shifts in suitability distribution of deciduous and citrus fruit trees under climate change in South Africa: a large-scale empirical study - Van Wyk, Ashlee (Department of Environmental and Geographical Science, 2026)
South Africa is the largest fresh fruit exporter by volume in the Southern Hemisphere. The quality and quantity of fruit produced depend on local climate, soil quality, water quality and availability. Climate change impacts may undermine the potential contributions of important fruit crops toward South Africa's foreign exchange earnings, national food security and local employment. This study assesses the likely impact of climate change on the future suitability of growing citrus and deciduous fruit in South Africa. 5 GCMs from the CORDEX ensemble were used to project future temperature and precipitation under a high- and a low-mitigation Representative Concentration Pathway (RCP4.5 and RCP8.5, respectively) for the periods 2031-2060 (mid-century) and 2071-2100 (end of century). The Ecocrop suitability model was used to project the changes in spatial suitability of 9 crops (oranges, lemons, mandarins, grapefruit, apples, pears, peaches, plums, and table grapes) over South Africa in each of these scenarios. Ecocrop is an empirical model, suited to this large-scale analysis despite known and acceptable point scale inaccuracies, and driven by changes in monthly minimum and mean temperatures and annual precipitation. The percentage of total land that was suitable for each fruit crop in each case was compared to historical suitability. For all crops, the largest changes in suitability were seen in END-85 due to extreme temperature increases. Large suitability increases were seen for oranges (341%) and lemons (279%), yet grapefruit and mandarins saw minor change (81% and 67% in END-85, respectively). Apples had small decreases in the east and increases over Lesotho highlands, having a net suitable land area of 78% in END85. Pears had moderate increases over Lesotho highlands and eastern escarpment and moderate decreases in the Lowveld, with a net increase of 126% of the suitable land area in END-85. Peaches and plums had weak decreases over the highveld and eastern escarpment, although the effects were stronger for plums, which gained 159% its suitable land area in END-85. Table grapes experienced negligible change. All of these effects were milder for the mid-century period and under RCP4.5 due to relatively less intense warming and drying. Indirect impacts of climate change include heat stress, water shortages, crop losses due to pest and disease proliferation, and changes in phenology